2015
DOI: 10.1016/j.ophtha.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Dry Eye

Abstract: openAccessArticle: Falsecover date: 2015-08-01pii: S0161-6420(15)00128-1Harvest Date: 2016-01-06 13:08:18issueName:Page Range: 1727-1727href scidir: http://www.sciencedirect.com/science/article/pii/S0161642015001281pubType: Repor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 4 publications
2
24
0
1
Order By: Relevance
“… 6 While most of these variables are relatively constant throughout the year, meteorological conditions vary by season. In fact, studies support a seasonal pattern in the prevalence of DE in the US 7 , 8 and other parts of the world. 9 Specifically, a nationwide retrospective analysis of US veterans found that the diagnosis of DE had a seasonal pattern, with the maximum prevalence in winter and spring.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“… 6 While most of these variables are relatively constant throughout the year, meteorological conditions vary by season. In fact, studies support a seasonal pattern in the prevalence of DE in the US 7 , 8 and other parts of the world. 9 Specifically, a nationwide retrospective analysis of US veterans found that the diagnosis of DE had a seasonal pattern, with the maximum prevalence in winter and spring.…”
Section: Introductionmentioning
confidence: 85%
“… 9 Specifically, a nationwide retrospective analysis of US veterans found that the diagnosis of DE had a seasonal pattern, with the maximum prevalence in winter and spring. 7 Yet, we still do not fully understand the role of seasonality in specific DE symptoms and signs.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, some glaucoma medications come in preservative-free, single-dose units, with reduced toxicity from chlorhexidine and SofziaR, and a decreased concentration of benzalkonium chloride (BAK), the most commonly used preservative in such agents [7]. DED are also multifactorial diseases that predominantly affect women and the elderly, rheumatoid disease, and immunological disease, and the seasonal variation in symptoms and signs of DED has been well documented [8][9][10][11]. Previous investigations have indicated that different seasons (spring, summer, and winter), cold and hot weather, seasonal air pollen, wind, and sunshine can exacerbate DED.…”
Section: Introductionmentioning
confidence: 99%
“… 1 – 4 Previous investigations have indicated that different seasons (spring, summer, and winter), cold and hot weather, wind, and sunshine may all exacerbate DED. 1 – 3 Air pollen is a seasonal environmental factor 3 that can induce allergic conjunctivitis, a problem that may be associated with DED. 5 , 6 A national survey demonstrated a close association between the severity of hay fever and elevated air pollen counts.…”
Section: Introductionmentioning
confidence: 99%